Proceedings of the International Conference on Social Modeling and Simulation, plus Econophysics Colloquium 2014 - Takayasu, Hideki; Ito, Nobuyasu; Noda, Itsuki; Takayasu, Misako (Springer Proceedings in Complexity,, 2015)
The proceedings of the international conference “SMSEC2014”, a joint conference of the first “Social Modeling and Simulations” and the 10th “Econophysics Colloquium”, held in Kobe in November 2014 with 174 participants, are gathered herein. Cutting edge scientific researches on various social phenomena are reviewed. New methods for analysis of big data such as financial markets, automobile traffics, epidemic spreading, world-trades and social media communications are provided to clarify complex interaction and distributions underlying in these social phenomena. Robustness and fragility of social systems are discussed based on agent models and complex network models. Techniques about high performance computers are introduced for simulation of complicated social phenomena. Readers will feel the researchers minds that deep and quantitative understanding will make it possible to realize comprehensive simulations of our whole society in the near future, which will contribute to wide fields of industry also to scientific policy decision.    .